Language dynamics in society (LanDS) - Ó Giollagáin, Conchúr (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2025)
Language Dynamics in Society (LanDS) is an analytical framework to reappraise ethnolinguistic vitality (EV) which is key to societal processes affecting the stability of language groups. LanDS proposes an enhanced academic analysis of EV and Language Promotion and Protection. This EV approach addresses the dynamics of how social players participate in the processes which are beneficial or detrimental to EV. LanDS posits four analytical Developmental Quadrants: Language Transmission and Acquisition, Socialisation and Reinforced Acquisition, Civic Expansion, and Coherent Ethnicisation. Each Quadrant is affected by the four core concepts of Direction, Process, Participation, and Competition. Collective community continuity or instability are shaped by the language group’s participation in these key developmental stages.
Keywords: družbena jezikovna dinamika; ethnicisation; ethnolinguistic vitality; etnično-jezikovna vitalnost; etničnost; LanDS framework; language transmission; manjšinska sociolingvistika; minority sociolinguistics; okvir LanDS; prenos jezika; societal language dynamics